Creative reception of biblical myths in the B. CHipchikov’s russian-language prose - Asiyat Dautovna Atabieva (Кавказология, 2023)
The purpose of this article is to look at the theosophical issues that are significant in modern realities considering examples of adaptation and qualitative reconstruction of religious plots, biblical mythologies, fragments from the scriptures in the works of the Russian-speaking author B. Chipchikov. This project seeks to identify antecedent religious inserts, quotations, and reminiscences in the works of the Balkarian prose writer. The research focuses on the semantics of biblical allusions, intertextual discourse, forms of figurative reflection on the world through mythotheologems. In the course of the analysis, the hidden meanings of the literary text, the ideological content of stories and short stories in the aspect of the sacred meanings inherent in them are revealed, the philosophical and symbolic images are deciphered from the point of view of their semiotic status, the subtext rolled up in them is read. The primary goal of the research is to determine the specifics of the writer’s individual perspective, as well as to define the ideological and creative foundations of his works. We attempted to describe the author’s anthropology’s humanistic essence, which consists in the proclamation of notions such as personal self-improvement, the value of human existence, the necessity of spiritual vision, intuitive feeling, rethinking the divine design, and many other related themes. The author’s intentionality and receptive aesthetics enable us to model a conditional picture of the world, artistically embodied in all of its contextual expressions.